2008
DOI: 10.1007/s11255-008-9416-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of PSA mRNA levels in peripheral blood of patients with localized prostate adenocarcinoma before, during, and after radical prostatectomy by quantitative real-time PCR (qRT-PCR)

Abstract: Our results suggest that highly detectable PSA mRNA expression levels in preoperative samples seem to be a significant predictable factor for prostate cancer recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“… 19 The clinical use of plasma PSA transcripts in PCa has already been investigated and it was found that highly detectable PSA mRNA expression levels in preoperative samples might indicate a potential risk for the recurrence of PCa. 27 It was also suggested that reverse transcriptase-PCR (RT-PCR)-measured PSA can be used as an effective predictor of PSA progression in men with mCRPC treated with chemotherapy. Ross et al.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The clinical use of plasma PSA transcripts in PCa has already been investigated and it was found that highly detectable PSA mRNA expression levels in preoperative samples might indicate a potential risk for the recurrence of PCa. 27 It was also suggested that reverse transcriptase-PCR (RT-PCR)-measured PSA can be used as an effective predictor of PSA progression in men with mCRPC treated with chemotherapy. Ross et al.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepant results were probably largely due to the qualitative nature of the RT‐PCR methods used in the early days. The development of absolute quantitative real‐time RT‐PCR in recent years has re‐invigorated the study of CTC detection in peripheral blood samples of patients with PCa 27, 43. Using such modern quantitative methods has generated sensitive assays for CTC analysis and now CTC detection is used as a secondary endpoint in drug development studies as investigators believe it is a valid surrogate marker of tumor activity and treatment response 22.…”
Section: Discussionmentioning
confidence: 99%
“…Longer follow-up is necessary to assess the clinical worth of detection of prostate-specific transcripts in the peripheral blood during brachytherapy as well as their effects on disease-specific survival. In comparison with the intra-operative RT-PCR results during radical prostatectomy, some authors have found significant correlations with tumor grade and stage [13] while others failed to show any significant correlations [16]. The significance of positive PCR reaction prior to brachytherapy is not clear and is likely not reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcriptase polymerase chain reaction (RT-PCR) has been investigated as a potentially new diagnostic, staging and prognostic modalities for prostate cancer [9][10][11]. The expression of prostatespecific genes was found elevated in the peripheral blood during urologic procedure including radical prostatectomy, transurethral or open prostatectomy and prostate biopsy [12][13][14][15][16]. However, the clinical significance of these results is controversial and is still unclear.…”
Section: Introductionmentioning
confidence: 99%